2017
DOI: 10.1002/ijgo.12334
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association of maternal smoking and passive smoking during pregnancy with neural tube defects

Abstract: Background: It is unclear whether the incidence of neural tube defects (NTDs) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
0
25
1
1
Order By: Relevance
“…By contrast, younger fathers were associated with NTD risk in our meta‐analysis, which might be due to the occurrence of unplanned pregnancies in this younger group who may not take folic acid supplementation and may engage in negative coping behaviors (Kazaura et al, 2004). Meng et al (2018) reported that passive smoking during pregnancy significantly increased the risk of NTDs. The present explanation for the young paternal age effect is that more unhealthy lifestyle among young couples may be prevalent, such as smoking and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, younger fathers were associated with NTD risk in our meta‐analysis, which might be due to the occurrence of unplanned pregnancies in this younger group who may not take folic acid supplementation and may engage in negative coping behaviors (Kazaura et al, 2004). Meng et al (2018) reported that passive smoking during pregnancy significantly increased the risk of NTDs. The present explanation for the young paternal age effect is that more unhealthy lifestyle among young couples may be prevalent, such as smoking and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven reviews (Table 3) described the health effects of second-hand smoke exposure during pregnancy [19,26,36,42,45,[48][49][50][51][52][53], three reviews ( Table 3) described health effects of using smokeless tobacco during pregnancy [43,44,54], while two reviews (Table 3) were about health outcomes of water pipe (shisha) use during pregnancy [46,55]. Association between postnatal maternal smoking and wheezing in the past 12 months had an effect size of 1.21 (95% CI: 1.13-1.31; I 2 = 47.0%, p = 0.067).…”
Section: Risks Associated With Exposure To Tobacco and Nicotine In Otmentioning
confidence: 99%
“…Similar to active smoking by pregnant mothers, the risk of orofacial clefts in infants was also accentuated by approximately 200% when mothers were exposed to passive smoking during pregnancy [51]. Babies exposed to passive smoking also have increased odds of neural tube defect (OR 1.898; 95% CI 1.557-2.313) [36].…”
mentioning
confidence: 99%
“…There are many other noxious compounds in tobacco smoke that can cross the placental barrier and influence prenatal development 27 . A metaanalysis showed that women exposed to SHS during pregnancy is associated with higher risk of infants’ neural tube defects 28 .…”
Section: Discussionmentioning
confidence: 99%